Conventional type 1 dendritic cells in the lymph nodes aggravate neuroinflammation after spinal cord injury by promoting CD8+ T cell expansion - Li-Qing Wang; Xiao-Yi Wang; Yue-Hui Ma; Heng-Jun Zhou (Molecular Medicine)
Abstract Background Adaptive immune response is at the core of the mechanism of secondary spinal cord injury (SCI). This study aims to explore the molecular mechanism by which classical dendritic cells (cDC1s) influence CD8+ T cell expansion in SCI. Methods Peripheral blood samples from patients with SCI and spinal cord tissues from SCI mice were collected, and the population of cDC1 subset was analyzed by flow cytometry. In vivo, the fms-like tyrosine kinase 3 (Flt3) inhibitor quizartinib was administered to deplete cDC1s, while intraperitoneal injection of recombinant Flt3L and immunosuppressive drug FTY-720 was used to expand cDC1s and prevent T cell egress from lymph nodes (LNs), respectively. In vitro, the conditioned medium (CM) of isolated LN fibroblastic stromal cells (FSCs) and pre-DCs were co-cultured. Subsequently, FSC CM-induced DCs were stimulated and co-cultured with CD8+ T cells for proliferation assay. Results The cDC1 subset was increased in the peripheral blood of SCI patients and in the injured spinal cord of SCI mice. Depletion of cDC1s decreased the proportion of infiltrating CD8+ T cells in the injured spinal cord of SCI mice and reduced the inflammatory response. The Basso Mouse Scale score of SCI mice was increased and the proportion of CD8+ T cells in blood and spinal cord tissue was decreased after FTY-720 injection. Both migratory cDC1s (CD103+) and resident cDC1s (CD8α+) were present in the LNs surrounding the injured spinal cord of SCI mice. Among them, CD103+ cells were derived from the migration of cDC1s in spinal cord tissues, and CD8α+ cDC1s were directionally differentiated from pre-DCs after co-culture with LN-FSCs. Interferon-γ promoted the secretion of Flt3L by LN-FSCs through the activation of JAK/STAT signaling pathway and enhanced the differentiation of pre-DCs into CD8α+ cells. Conclusion Migratory cDC1s and resident cDC1s promote the expansion of CD8+ T cells in LNs around the injured spinal cord and mediate the adaptive immune response to aggravate neuroinflammation in SCI.